Phytotoxic effects of aqueous leaf extracts of Cosmos sulphureus Cav. on Sorghum bicolor L, Vigna aconitifolia L, Triticum aestivum L. - Gharpure, Pallavi; Vaishali, Bansod; Nivedita, Ghayal (Journal of Tropical Agriculture, 2024)
Weeds nearby crop fields are considered as unwanted noxious plants and exhibit many harmful effects on growth, germination and physiology of cultivated crops. Cosmos sulphureus Cav. is widely distributed dominant weed and is found in abundance after onset of monsoon. The present study was conducted to assess its allelopathic effects by using aqueous leaf extracts on various germination parameters of Sorghum bicolor L. (Moench) (jowar), Vigna aconoitifolia L. (moth bean) and Triticum aestivum L. (wheat) from Pune district. At lower concentrations (50%) stimulatory effects were observed while inhibitory effects were observed at higher concentration on germination of Triticum aestivum (20%), Sorghum bicolor (46%) Vigna aconitifolia (70%). Germination percentage, root length-shoot length and vigor index were significantly reduced with increasing concentrations. Root length, shoot length were at par with control at lower concentrations (50%) but as concentrations increased gradual reduction in parameters was observed in jowar and wheat, whereas moth bean exhibited moderate reduction in germination of seeds. Phytochemical analysis of aqueous crude extract showed presence of alkaloids, phenols, tannins, flavonoids, proteins, amino acids in varying amounts while saponins were absent. The variations in phytochemicals can be attributed to response of the plants to different environmental stresses as abiotic and biotic factor and mainly the geographical location. Thus, as per the results obtained Cosmos sulphureus exhibits allelopathic effects on germination and growth of Sorghum bicolor, Triticum aestivum and Vigna aconitifolia from Pune district.